Inovasi Pengembangan Media Kuis Pada Pembelajaran Bahasa Sunda Berbasis Android - Maesyaroh, Siti (JATISI, 2025)
Quiz are an evaluation medium given during the learning process in Sundanese language subjects to test students' knowledge. Sundanese is the language used by Sundanese people to communicate. At SMPN 1 Cibeureum, there are Sundanese language subjects that use Google Forms in conducting quizzes as an evaluation medium. With this media there are obstacles, namely that students can take the quiz several times using another email account, to limit the time for completing questions, there are features that must be installed so it takes time, and questions cannot be created with different value weights. In this research, the author created an Android-based quiz on Sundanese language subjects that applies system development methods with an agile approach. This method includes application development stages that actively involve users. The results of system testing show that the average index in usability testing for positive statements is 92.6% and negative statements is 26.2%. From the index value obtained, it can be stated that the quiz application has achieved the goals and user experience because the test value is above the specified standard.